2020
DOI: 10.23887/jpi-undiksha.v9i1.19222
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoconstructivism E-Module to Improve Perception, Interest, and Motivation of Students in Class v Elementary School

Abstract: This study aims to develop instructional media in the form of teaching materials in the form of electronic modules by using the Pageflip Professional 3D software application for fifth-grade elementary school students. The method in this study uses the Research and Development (R & D) method that adapts the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the assessment in this study on the questionnaire obtained the frequency perception of 28 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 0 publications
5
103
0
35
Order By: Relevance
“…Melalui proses pendidikan, kognitif seseorang akan menjadi luas dan bertambah. Pendidikan dapat menjadi tolak ukur kualitas sumber daya manusia (Asrial, dkk, 2020). UU no 20 tahun 2003 (Praditya, 2019) menyatakan bahwa pendidikan merupakan usaha sadar serta terencana dalam mewujudkan suasana belajar aktif sehingga siswa dapat mengembangkan potensi dan kepribadiannya kearah yang lebih baik.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Melalui proses pendidikan, kognitif seseorang akan menjadi luas dan bertambah. Pendidikan dapat menjadi tolak ukur kualitas sumber daya manusia (Asrial, dkk, 2020). UU no 20 tahun 2003 (Praditya, 2019) menyatakan bahwa pendidikan merupakan usaha sadar serta terencana dalam mewujudkan suasana belajar aktif sehingga siswa dapat mengembangkan potensi dan kepribadiannya kearah yang lebih baik.…”
Section: Pendahuluanunclassified
“…E-modul merupakan bahan ajar yang dikemas secara digital. E-modul dapat membantu guru memfasilitasi siswa dalam belajar (Asrial, dkk, 2020;Citrawathi, dkk, 2016). (Diantari, dkk, 2018;Udayana, dkk, 2017) menyatakan bahwa E-modul merupakan media pembelajaran digital yang disusun sistematis sehingga siswa dapat belajar mandiri dan memecahkan masalah yang ada.…”
Section: Pendahuluanunclassified
“…One of the subjects that require independence is productive subjects. So it can be concluded that the existence of an electronic module can add learning media that can help students explore knowledge and deepen practical knowledge (Asrial, Syahrial, Maison, Kurniawan, & Piyana, 2020;Diantari, Damayanthi, Sugihartini, & Wirawan, 2018). Principles of electronic module development.…”
Section: Introductionmentioning
confidence: 99%
“…Then, research on the development of 3D-Pageflip media has a valid and reliable category to be used in teaching [32], but this research was only limited to develop the media and was not tested in learning. Then, the use of 3D-Pageflip media has a good influence on students' interest and motivation in the learning process [52], but this research did not see the effect on SAA. However, the use of 3DP-LM in this research has a good effect on SAA.…”
Section: Kogomorov-smirnov Conclusionmentioning
confidence: 56%